2015 IEEE First International Conference on DC Microgrids (ICDCM) 2015
DOI: 10.1109/icdcm.2015.7152004
|View full text |Cite
|
Sign up to set email alerts
|

Solar-DC deployment experience in off-grid and near off-grid homes: Economics, technology and policy analysis

Abstract: India is a power deficit country and one third of its homes are off grid or near off grid. This paper presents an efficient and affordable Solar DC solution for powering such homes. Though several solutions have emerged in the past for powering these homes, those have been expensive and energy inefficient. These solutions rely on several DC to AC and AC to DC conversions, to feed the widely used AC home loads, thus, wasting a large chunk of the expensive power. The proposed Solar DC solution for off-grid homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…protection schemes) [75] which complicates a direct comparison of different networks without more information on their characteristic. However, DC has a second simplicity benefit which is the reduced number of power conversion phases required in PV-supplied systems resulting in significant energy efficiency gains [76] [77]. Energy efficiency makes DC distributed PV power grids more energy frugal by architecture.…”
Section: Definitionmentioning
confidence: 99%
“…protection schemes) [75] which complicates a direct comparison of different networks without more information on their characteristic. However, DC has a second simplicity benefit which is the reduced number of power conversion phases required in PV-supplied systems resulting in significant energy efficiency gains [76] [77]. Energy efficiency makes DC distributed PV power grids more energy frugal by architecture.…”
Section: Definitionmentioning
confidence: 99%
“…An effective Maximum Power Point Tracking (MPPT) algorithm to obtain constant DC voltage of 12 V or 24 V using a PI controller is studied in [6]. An Off Grid Home (OGH) which is inverter less system to power lighting loads are deployed in [8].…”
Section: Existing Work In DC Microgridsmentioning
confidence: 99%
“…In rural areas, usually the application side dispersal transformer having a 20% to 25% reduced voltage than the general fixed values. Operation of conventional induction motor based devices like household fans with such voltage variation from the general fixed values may results in higher iron losses, which may leads to the permanent damage of motor [8]. The calculated values of various converter parameters for energizing <24 V devices are tabulated in Table 2.…”
Section: Loads With <24 V Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied showed that the DC system is more efficient and also brings cost savings for the users, by reducing the electricity bills, and the cost of the system. In [20], the conceptual implementation of low power solar system is shown. The system is designed to cover the minimum needs of a low-income household in India.…”
Section: B Unipolar Low Voltage DC Distribution Systemsmentioning
confidence: 99%